Suspected Nonalcoholic Fatty Liver Disease Is Not Associated with Vitamin D Status in Adolescents after Adjustment for Obesity - Karin Katz; Preneet Cheema Brar; Niyati Parekh; Ying-Hua Liu; Michael Weitzman (Journal of Obesity)
This study investigated a potential independent association between hypovitaminosis D and suspected nonalcoholic fatty liver disease (NAFLD) in a nationally representative sample of the US adolescents. Data from 1630 subjects 12–19 years of age were examined using the National Health and Nutrition Examination Survey, 2001–2004. The vitamin D status of subjects was categorized into quartiles of serum 25-hydroxyvitamin D. Subjects with serum ALT>30 U/L were classified as having suspected NAFLD. Data regarding age, sex, race, BMI, and poverty level were also analyzed in bivariate and multivariate analyses using SAS and SUDAAN software. Suspected NAFLD was identified in 12.1% of adolescents in the lowest quartile compared to 6.9% of adolescents in the second quartile, 8.0% in the third quartile, and 13.17% in the highest quartile of serum 25(OH)D concentrations (𝑃=.05). In analyses utilizing vitamin D as a continuous variable, no independent association was found between Vitamin D levels and rates of elevated ALT levels. In multivariate analyses, higher risks for suspected NAFLD were observed in males and overweight adolescents; however, vitamin D status was not found to be independently associated with suspected NAFLD after adjusting for obesity.